Evaluation of Functional Outcomes after Stapes Surgery in Patients with Clinical Otosclerosis in a Teaching Institution - Souza,José Celso Rodriques de (2016)
Introduction Otosclerosis is a primary disease of the temporal bone that leads to stapes ankylosis. Hearing loss is the main symptom. Treatment includes surgery, medical treatment, and sound amplification therapy alone or in combination. Objective To evaluate the functional outcomes of patients with clinical diagnosis of otosclerosis undergoing primary stapes surgery in a teaching institution. Method Retrospective descriptive study. Results A total of 210 ears of 163 patients underwent stapes surgery. Of the 163 patients, 116 (71.2%) underwent unilateral surgery and 47 (28.8%) underwent bilateral surgery. Six of the 210 operated ears had obliterative otosclerosis. The average preoperative and postoperative air-bone gap was 32.06 and 4.39 dB, respectively. The mean preoperative and postoperative bone conduction threshold was 23.17 and 19.82 dB, respectively. A total of 184 (87.6%) ears had a residual air-bone gap <10 dB, and 196 (93.3%) had a residual air-bone gap ±15 dB. Two patients (0.95%) had severe sensorineural hearing loss. Conclusion Stapes surgery showed excellent functional hearing outcomes in this study. This surgerymay be performed in educational institutions with the supervision of experienced surgeons.